Economic feasibility of recirculating aquaculture systems in pangasius farming. Issue 2 (2nd April 2016) - Ngoc, Pham Thi Anh; Meuwissen, Miranda P. M.; Cong Tru, Le; Bosma, Roel H.; Verreth, Johan; Lansink, Alfons Oude
ABSTRACT: This study aims to analyze the economic feasibility of recirculating aquaculture systems (RAS) in pangasius farming in Vietnam. The study uses a capital budgeting approach and accounts for uncertainty in key parameters. Stochastic simulation is used to simulate the economic performance of medium and large farms operating with a traditional system or RAS. Data are obtained through structured surveys and a workshop in the Mekong River Delta. Results show that for large farms, net present value increases from an average of 589, 000 USD/ha to 916, 000 USD/ha after implementing RAS. Overall, the probability that RAS is a profitable investment is found to be 99% for both farm sizes. With RAS, the crucial parameters determining profitability are price, yield, costs of fingerling, feed, and initial investment. Findings on the robustness of the economic performance of RAS are useful to support public and private decision making towards increasing the sustainability of pangasius production.